Riding the Adolescence: Personality Subtypes in Young Moped Riders and Their Association With Risky Driving Attitudes and Behaviors - Lucidi, Fabio; Mallia, Luca; Giannini, Anna Maria; Sgalla, Roberto; Lazuras, Lambros; Chirico, Andrea; Alivernini, Fabio; Girelli, Laura; Violani, Cristiano (Frontiers in Psychology, 2019)
The present study aimed to identify, within a large sample of Italian adolescents, sub-types of moped riders based on a cluster analysis of personality traits (i.e., driving anger, anxiety, angry hostility, excitement-seeking, altruism, normlessness and driving locus of control). A secondary aim of the study was to compare the emerged sub-types of moped riders on measures of attitudes towards safe driving, risky driving behaviours (e.g. rule’s violations and speeding, not using helmet, drinking and driving, etc), and self-reported tickets and accident involvement. One thousand two hundred seventy-three Italian high school students aged from 13 to 19 years (mean age = 15.43, SD = .98) with a valid driving license for moped participated to the study. Based on a cluster analysis of the personality traits, three subgroups of moped riders were identified (risky, worried and careful moped riders). The three groups displayed statistically significant differences in self-reported risky driving behaviours, attitudes toward traffic safety, risk perception, and self-reported accident involvement. Importantly, the results of the study showed that the personality and behavioural characteristics of the three sub-types of moped riders substantially resembled those identified by previous studies with vehicle drivers of different ages; thus, empirically supporting the notion that certain combinations of personality characteristics are associated with risk driving tendencies and behaviours in both young moped riders and car drivers. Safe driving interventions can tackle risky driving beliefs and behavioural tendencies in young moped riders and car drivers by tailoring their messages according to the personality sub-types of the target groups.